Fiheries Business Development Strategy of PT Samudera Kencana Mina Sidoarjo - Muhammad Erianto Septayadi; Idqan Fahmi; Arief Safari (Budapest International Research and Critics University, 2022)
The performance of the Indonesian fishing industry has a significant impact on the performance of fishing companies, one of which is PT Samudera Kencana Mina. The company's revenue in the 2015-2021 period recorded fluctuating growth following the movement of global and national fishery trade. This research is intended to create a related strategy to improve the performance of PT Samudera Kencana Mina. Seeing some of the problems that exist, PT Samudera Kencana Mina needs to carry out a business development strategy during and after COVID-19 by considering conditions before the Covid-19 pandemic. The data collection techniques used were observation, FGD, interviews and questionnaires from the management of PT Samudera Kencana Mina. The data obtained will be used to analyze the IFE, EFE and IE matrix which are compared with the SWOT analysis. Both analyzes are followed by a Quantitative strategic planning matrix (QSPM) to find out what strategies are the top priorities. The results of the research using the IE matrix show that the company is in quadrant 2 with the more recommended strategy being integrative and intensive. The SWOT strategy analysis resulted in 8 alternative strategies with the priority strategy is increase production capacity.